Genetic Endowments, Educational Outcomes and the Mediating Influence of School Investments - Benjamin W. Arold; Paul Hufe; Marc Stoeckli (Center for Economic Studies and ifo Institute (CESifo), 2022)
Genetic endowments are fixed at conception and matter for the educational attainment of individuals. Do investments in schooling environments mitigate or magnify the outcomes of this genetic lottery? Using data from a representative sample of US adolescents, we analyse the interdependent associations of genetic endowments, teacher quality and teacher quantity with educational attainment. Our results suggest that higher-quality teachers act as substitutes for genetic endowments: a 1 SD increase in teacher quality reduces the positive association between educational attainment and a 1 SD increase in the relevant polygenic score from 0.37 to 0.30 years—a decrease of 20%. In particular, high-quality teachers increase the probability that genetically disadvantaged students complete college. This increase is underpinned by gains in health, language ability, patience, and risk aversion.
Keywords: I29; I21; J24; 330; polygenic scores; school resources; skill formation